Genetic variability of forage characters in genus Paspalum accessions in different environments (Semiárida, 2020)
The objective of this study was to determine the genetic variability among accessions of different species of Genus Paspalum, seeking to understand the dynamics of expression of characters with forage interest in different locations and crop years. The experiments were conducted in randomized blocks with three replications and plots consisting of five accessions of P. nicorae two of P. guenoraum and more to cultivate Pensacola (P. notatum) used as a control. The accessions show high genetic variability in forage traits of interest, with a decisive effect on the expression of the genotype versus environment interaction.
Keywords: Native species; Genotype x environment interaction; Selection